2014
DOI: 10.1088/0953-2048/27/4/044004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SQUIDs on functional imaging in neuroscience

Abstract: This paper provides an overview on the basic principles and applications of magnetoencephalography (MEG), a technique that requires the use of many SQUIDs and thus represents one of the most important applications of superconducting electronics. Since the development of the first SQUID magnetometers, it was clear that these devices could be used to measure the ultra-low magnetic signals associated with the bioelectric activity of the neurons of the human brain. Forty years on from the first measurement of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 118 publications
0
1
0
Order By: Relevance
“…Each sampling point consists of one (magnetometer or axial gradiometer) or multiple (magnetometer and two orthogonal planar gradiometers) detection channels. A review of the existing MEG systems can be found in Della Penna et al (2014). To reduce the contribution of the environmental magnetic field (noise) to the measured field, MEG systems are usually operated inside a magnetically shielded room.…”
Section: Box 2 -Instrumentation For Megmentioning
confidence: 99%
“…Each sampling point consists of one (magnetometer or axial gradiometer) or multiple (magnetometer and two orthogonal planar gradiometers) detection channels. A review of the existing MEG systems can be found in Della Penna et al (2014). To reduce the contribution of the environmental magnetic field (noise) to the measured field, MEG systems are usually operated inside a magnetically shielded room.…”
Section: Box 2 -Instrumentation For Megmentioning
confidence: 99%